Reviews and notices - Connor, Steven; Hedberg, Johannes; Wintle, Sarah; Murray, Christopher; Miller, Jeffrey S.; Smith, Lindsay; Sawyer, Birgit; Overton, Bill; Wright, David; Mobärg, Mats; et al. (Moderna Språk, 1991)
Includes the following reviews: pp. 84-86. Steven Connor. Zadworna-Fjellestad, D. & Björk, L. (eds), Criticism in the Twilight Zone: Postmodern Perspectives on Literature and Politics. pp. 86-87. Johannes Hedberg. Allen, R.E. (ed), The Concise Oxford Dictionary of Current English (8th ed). pp. 88-89. Sarah Wintle. Thurin, E.I., The Humanization of WIlla Cather: Classicism in an American Classic. pp. 89-90. Christopher Murray. Pine, R., Brian Friel and Ireland’s Drama. pp. 91-92. Jeffrey S. Miller. Buxton, D., From The Avengers to Miami Vice: Form and Ideology in Televison Series. pp. 93-94. Lindsay Smith. Fawkner, H.W., Deconstructing Machbeth: The Hyperontological View. pp. 94-96. Birgit Sawyer. Owen-Crocker, G., Dress in Anglo-Saxon England. pp. 96-97. Bill Overton. Super, R.H., The Chronicler of Barsetshire: A Life of Anthony Trollope. + Bell, A.C., A Guide to Trollope. pp. 97-98. David Wright. Neaman, J.S. & Silver, C.C., Kind Words: A Thesaurus of Euphemisms. pp. 98-99. Mats Mobärg. Room, A., An A to Z of British Life. pp. 99-100. Gösta Werner. Schröder, F., Die Gestalt des Verführers im Frama Hugo von Hofmannsthals. pp. 101-102. Ulrike Klingemann. Wimschneider, A., Herbstmilch. Lebenserinnerungen einer Bäuerin. pp. 103-105. Gustav Korlén. Landin, P., Von dort nach hier. Zum Prozeß der Vermittlung deutschsprachiger Belletristik in Schweden 1980-1988. pp. 106-110. Sven Sandqvist. Picoche, J. & Machello-Nizia, C., Histoire de la langue française. pp. 110-112. Ken Bensson. Casado, P.G., La novela deshumanizada española (1958-1988).